(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
The article presents the normative values of the consumption of saturated water steam for steaming beech lumber with false heartwood wood of thickness h = 40 mm by a volume of 16 m3 in pressure autoclave AZ 240 for the purpose of eliminating color differences between sapwood and false heartwood by steaming modes I. and II. The norm of water steam consumption for the steaming process of beech wood using mode I, uniting the wood to a light brown color, is m H2O-I = 2637.6 kg. Normative heat consumption for the process of steam mode II. to dark brown-gray color is m H2O-II = 3051.9 kg. The discontinuous process of steaming wood in an autoclave is characterized by uneven consumption of saturated water steam, the largest consumption is at the beginning of the technological process when heating the steamed wood and the autoclave. In the heating phase, in the most demanding mode of steam consumption, mode II, m H2O = 856.4 kg.h-1 steam is consumed. After heating, the consumption of saturated steam drops significantly to m H2O = 6.1 kg.h-1 . The practical benefit of specifying the consumption of saturated water steam in the process of steaming wood in a steam autoclave is when planning the production of heat in the heat source – the boiler room of the plant and the capacity load of the waste water treatment plant.